Analisis Zonasi Ekowisata Bahari Berbasis Sistem Informasi Geografis - Ahmad Herison; Yuda Romdania; Willy Brilliant Yosua (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2018)
The magnitude of tourism potential and diversity of tourism in Pesisir Barat District, making the attraction for tourists in Pesisir Barat District. It is needed a tourism planning in the mapping of marine ecotourism area in Pesisir Barat District, beauty of nature, and the interest of foreign tourists are not hindered by the attributes - ecotourism attributes that are inadequate for the purpose of the prosperity that has a big impact for the province and the country. The purpose of this research is to design the zoning of marine ecotourism area in Pesisir Barat regency. The method used is Community Based Analysis Method and SWOT Analysis based on Geographic Information System. Based on the analysis, this regency has 30 areas that have the potential to be developed. It can be concluded that special attention is needed from the government in arranging space and territory in natural resources owned by Pesisir Barat regency.